Variation and change in the grammatical marking of stance - Godnič Vičič, Šarolta (ELOPE (Ljubljana), 2015)
Variation in the genre of research articles has been extensively studied across different disciplines and languages; however, diachronic change and intradisciplinary variation in this academic genre have received less attention. Therefore this paper aims to shed light on change and variation in research articles within a multidisciplinary field of research by focusing on the use of thatcomplement clause constructions which are known to mark stance. The corpus-based study uses tourism studies as an example, and covers the time span from 1995 to 2010. Diachronic change in the use of that-complement clause constructions was found in instances when they are marked by a verb as well as in the kinds of stance meanings conveyed. Significant intradisciplinary variation was also found across the journals.
Keywords: besediloslovje; diahrono spreminjanje; stavčne strukture vrednotenja z "that"; Text linguistics; variiranje; vrednotenje; znanstveni članki